Penilaian Kesesuaian Lahan untuk Tanaman Jagung dan Kedelai di Lahan Rawa Lebak Desa Tanjung Sejaro Kecamatan Indralaya Kabupaten Ogan Ilir - Marizal Ijal; Warsito; Satria Jaya Priatna (Universitas Merdeka Madiun, 2023)
This study aims to assess the suitability of land for corn and soybean plants. The research has been carried out in January to March 2020 in the swampy land of Tanjung Sejaro Village, Indralaya District, Ogan Ilir Regency. This research uses an intensive level survey method with an area of 5 ha. Observation and measurement were made directly to the field using a 1: 5000 scale map. The sample points consist of 10 points taken by the grid method, at each point representing 0.5 ha. Soil samples taken at a depth of 0-20 cm from the ground surface. The variables observed in the field were that the drainage class was rather poor, the effective depth was generally >90 cm, the topography was flat (<3%). The parameters observed in the laboratory were chemical properties in the form of very acidic soil pH in the range of 3.97-4.37, CEC classified as low with a range of 7.50-15.00 cmol/kg, Total nitrogen was very low with a range of 0.01-0.08 %, Phosphorus available was classified as very low with a range of 0.25-4.60 ppm, Potassium available was classified as very low with a range of 0.19-0.38 cmol/kg. The results showed the actual suitability for corn and soybean plants was N (not suitable) with several factors limiting nutrient retention and available nutrients. If liming and fertilizing inputs are given, the potential suitability for corn and soybean plants is S2.